Design and performance evaluation of an anaerobic sludge blanket reactor with mechanical mixing system and a high-rate settler treating domestic wastewater - Pessotto, Bruno (2015)
The UASB (Upflow Anaerobic Sludge Blanket) reactor, developed by Prof. Gatze Lettinga and his colleagues in the Netherlands more than thirty years ago, is successfully employed in many sewage treatment plants in countries with tropical and subtropical climate. However, are still reported serious operational issues related to the three-phase separators and problematic aspects involving the complexity of its influent distribution system. The focus of this research was to simplify the introduction and dispersion of the sewage in the reactor as well as enhancing the sludge retention, by replacing the characteristic piping system for a mechanical mixing apparatus and substituting the (conventional) three-phase separators by a high-rate settler, respectively. In essence, it was proposed a system partitioned into two distinct regions: one for reaction (i.e. anaerobic digestion of organic matter), in which the sludge blanket was mechanically mixed through the action of a rotating impeller, and another for the removal of suspended solids by the use of a lamella plate clarifier; a sludge recirculation system was also implanted, to pump the settled biomass back to the digestion compartment. The research was subdivided into three main phases: in the first two phases, bench-scale experiments were performed in order to obtain basic data for the design of the mechanical mixing and sedimentation devices, while the third phase consisted of the application of these technologies in a pilot-scale system with total volume of 20.8 m3 (comprised of a 17.0 m3 digestion chamber and a 3.8 m3 compartment for solids removal), as well as its performance assessment. During the development of the research, domestic sewage was applied to feed the experimental system, which was located at the School of Engineering of São Carlos (Campus I) in São Carlos (São Paulo State, Brazil). Throughout the period of effective operation, which lasted 130 days, four distinct operating modes were tested (characterized by intermittent mixing and varying hydraulic loading rates, ranging between 27.6 and 66.5 m3.d-1) and the system reached maximum removal efficiencies of BOD, COD and TSS at rates of 82%, 72% and 83%, respectively. The high-rate settler presented an impressive efficiency removing suspended solids (rates up to 98%). The research showed that the new \"Anaerobic Activated Sludge Blanket\" system (A2SB) can provide satisfactory performance even operating without the three-phase separator and influent distribution system.